The use of Oxaliplatin or Mitomycin C in HIPEC treatment for peritoneal carcinomatosis from colorectal cancer: A comparative study. Issue 6 (28th December 2013) - Hompes, D.; D'Hoore, A.; Wolthuis, A.; Fieuws, S.; Mirck, B.; Bruin, S.; Verwaal, V.
Abstract Background Oxaliplatin and Mitomycin C (MMC) are both suitable as intraperitoneal chemotherapy agents in HIPEC for peritoneal carcinomatosis (PC) of colorectal cancer (CRC). Methods Patient cohorts from two different HIPEC‐centers underwent cytoreductive surgery and HIPEC with Oxaliplatin (39 patients) and MMC (56 patients), respectively. They were compared for toxicity and survival data. The extent of PC was assessed using the Dutch 7‐region count. Results The median 7‐region count was 4 [range 0–7] for Oxaliplatin‐patients versus 2.5 [range 1–6] for MMC‐patients (P = 0.004). Median intra‐operative blood loss was 650 ml [0–6, 000 ml] in Oxaliplatin‐patients versus 1, 230 ml [range 0–5, 300 ml] in MMC‐patients (P < 0.001). Only MMC‐patients developed neutropenia/leucopenia (26.8%, P < 0.001). After statistical correction for the extent of PC, the overall postoperative complication rate was significantly higher in MMC‐patients (OR = 2.68 (95% CI: 1.04–6.91), P = 0.04), with a comparable intra‐abdominal complication (IAC) rate (OR = 0.78 (95% CI: 0.30–2.03), P = 0.61), but a tendency towards more extra‐abdominal complications (EAC) in MMC‐patients (OR = 2.23 (95% CI: 0.91–5.43), P = 0.079). Median follow‐up was significantly shorter for Oxaliplatin‐patients (2.8 years) than for MMC‐patients (5.1 years). Median RFS was 12.2 months [IQR: 7.2‐undefined] in the Oxaliplatin‐group and 13.8 months [IQR: 7.0–25.8] in the MMC‐group (P = 0.87). Median OS is 37.1 months [IQR: 22.4–52.8] for Oxaliplatin‐patients and 26.5 months [IQR: 16.9–64.8] for MMC‐patients (P = 0.45). Logistic regression analysis (corrected for extent of PC) shows RFS (HR = 1.24 (95% CI: 0.75–2.05), P = 0.39) and OS (HR = 1.37 (95% CI: 0.74–2.54), P = 0.32) are not significantly different. Conclusions No clear benefit in RFS and OS for HIPEC with Oxaliplatin or MMC could be demonstrated in patients with PC from CRC. J. Surg. Oncol. 2014 109:???–???. © 2013 Wiley Periodicals, Inc.